2022
DOI: 10.1097/md.0000000000028869
|View full text |Cite
|
Sign up to set email alerts
|

Adenosine triphosphate-binding cassette subfamily C members in liver hepatocellular carcinoma

Abstract: Aberrant expression of adenosine triphosphate-binding cassette subfamily C (ABCC), one of the largest superfamilies and transporter gene families of membrane proteins, is associated with various tumors. However, its relationship with liver hepatocellular carcinoma (LIHC) remains unclear.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
3
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 65 publications
0
3
1
Order By: Relevance
“…Astrocytes only exist in the central neuron system, which may explain the results of our study. Regarding the studies focusing on ABCC8 and cancer immunity, there was only one study by Meng et al (2022) was found on the PubMed website, which reported a positive correlation of ABCC8 with CD4+ T-cell and macrophage infiltration and a negative correlation with OS in liver hepatocellular carcinoma, totally opposite to our results, probably due to the different tumor backgrounds.…”
Section: Discussioncontrasting
confidence: 99%
“…Astrocytes only exist in the central neuron system, which may explain the results of our study. Regarding the studies focusing on ABCC8 and cancer immunity, there was only one study by Meng et al (2022) was found on the PubMed website, which reported a positive correlation of ABCC8 with CD4+ T-cell and macrophage infiltration and a negative correlation with OS in liver hepatocellular carcinoma, totally opposite to our results, probably due to the different tumor backgrounds.…”
Section: Discussioncontrasting
confidence: 99%
“…In the era of precision medicine, identification of biomarkers that have a predictive value for targeted therapies may improve clinical outcomes 2 . ABCC2 is part of the family of ABC transporter/multidrug resistance proteins, implicated in chemotherapy resistance in various tumours 21–24 . ABC proteins also play an active role, beyond multidrug resistance, in tumour development and aggressiveness 18 .…”
Section: Discussionmentioning
confidence: 99%
“…2 ABCC2 is part of the family of ABC transporter/multidrug resistance proteins, implicated in chemotherapy resistance in various tumours. [21][22][23][24] ABC proteins also play an active role, beyond multidrug resistance, in tumour development and aggressiveness. 18 Our previous study using in vitro and in vivo experiments on PRCC2 cell lines showed that MK571, an ABCC2 blocker, on its own showed a significant response to therapy, suggesting that ABCC2 may contribute to tumour growth.…”
Section: Discussionmentioning
confidence: 99%
“…Regarding the role of ABCC6 in hepatocellular carcinoma, a recent study demonstrated that low expressions of ABCC6 and other ABCC transporters are correlated with poor prognoses in liver hepatocellular carcinoma, identifying these proteins as potential diagnostic markers [21]. Zhao et al reported that ABCC6 is down-regulated in HCC tumor tissues and correlates with favorable outcomes in patients with HCC [22].…”
Section: Introductionmentioning
confidence: 99%